Implementation of Zakat Village Index method in Bolang Village - Muhammad Syaswan; Muhammad Nasri Katman; A. Syatir Sofyan; Nur Asyah Muhtar (IECON: International Economics and Business Conference, 2024)
The title of this research is "Implementation of the Village Zakat Index Method in Measuring the Level of Community Welfare in Bolang Village, Alla District, Enrekang Regency". This title aims to answer the question of whether or not Bolang Village, Alla District, Enrekang Regency is eligible to receive zakat funds from BAZNAS. The type of research used in this study was conducted in Bolang Village, Alla District, Enrekang Regency. Enrekang Regency. The data collection method used is through questionnaires, interviews and documentation given directly to stakeholders in Bolang Village, namely the local government. Then the data was analyzed using quantitative descriptive methods. The results of the study showed that the index value of each variable where the value of the Economic Dimension (0.26), Health Dimension (0.78), Education Dimension (0.73), Social and Humanitarian Dimension (0.48), Empowerment Dimension (0.48), and Social and Humanitarian Dimension (0.48). (0.48), Da'wah and Advocacy Dimension (0.81). Then the calculation of the accumulated value of the Village Zakat Index (IDZ) in Bolang Village, Alla District, Enrekang Regency, obtained an IDZ value of 0.58. And if categorized into the Score Range, Bolang Village is included in the Fairly Good category. Which means that Bolang Village can be said to be worthy of assistance, especially in the economic dimension of the village in order to improve the welfare of its people. The Bolang Village Government is expected to be able to implement programs that can improve the welfare of its people, such as the formation of creative economic activists.